A sub-milligram-synthesis protocol for in vitro screening of HDAC11 inhibitors. Issue 10 (15th May 2016) - Tian, Yinping; Jin, Jin; Wang, Congying; Lv, Wenhui; Li, Xuewei; Che, Xiaona; Gong, Yanchao; Li, Yanjun; Li, Quanli; Hou, Jingli; Wang, Peng G.; Shen, Jie
Graphical abstract: Abstract: This work demonstrated the high efficiency of a sub-milligram-synthesis based medicinal chemistry method. Totally 72 compounds, consisting a tri-substituted pyrrolidine core, were prepared. Around 0.1 mg of each compound was solid-phase synthesized. Based on the additive property of UV absorptions of unconjugated chromophores of a molecule, these compounds were quantified by UV measurement. A hit, whose IC50 value was 1.2 μM in HDAC11 inhibition assays, highlights the applicability of the approach reported here in future optimization works.